Implementasi Metode Demonstrasi Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Fiqih Kelas VIII Di Mts Emeyodere Kota Sorong - Harisah, Akramun Nisa (Al-Riwayah : Jurnal Kependidikan, 2015)
MTS Emeyodere is one of the schools built in Sorong. Most students of this school came from local population especially the Kokoda tribe. Most of the students have weak ability and understanding. It is relevant to conduct a research based on the conditions that exist at the school. This research uses classroom action research. The research conducted through two cycles. The first cycle starts on planning, implementation, application, observation and reflection. Second cycle is quiet similar with the first cycle. Data collection of this research is observation, test and documentation. Techniques of data analysis use percentage descriptive analysis which were analyzed twice by an analysis of individual learning and classical learning mastery.The result of the research indicates that the implementation of demonstrative method can increase students’ Figih ability. In the first cycle, the data can be obtained average 65,35 and students learning mastery as much as 42,9%. The second cycle shows that the average values obtained is 71,42 with learning mastery 75%. The data shows that there is a significant difference between before using demonstrative method and after being tough using demonstrative method.